Price Discrimination in Dynamic Cournot Competition. (25th June 2019) - Zhang, Wei-li; Song, Qi-Qing; Jiang, Yi-Rong
Abstract : This paper introduces a new Cournot duopoly game and gives an applied study for price discrimination in a market by dynamic methods. One of two oligopolies has two different prices for a homogeneous product, while the other charges one kind of price. It is found that there is only one stable equilibrium for the discrete dynamic system, and a corresponding stable condition is given. Using a discriminative price is not always beneficial to a firm in equilibrium. If both oligopolies carry out price discrimination, the market's average price is lower than when only one oligopoly does it. The results are verified by numerical simulations.